IIoT-Enabled Coopetition Networks for Enhancing Manufacturing Efficiency in SMEs: An Applied System Innovation Approach - da Silva, Agostinho; Pata, A.; Duarte de Almeida, I. (Applied System Innovation, 2026)
This study investigates whether coopetition networks enhance manufacturing efficiency in Small and Medium-sized Enterprises (SMEs), using Portuguese Ornamental Stone firms as an empirical case. Grounded in Service-Dominant Logic and Open Innovation, the research examines how val-ue co-creation and resource integration within a technology-enabled coopetition network influ-ence key efficiency determinants. A two-phase data collection process was conducted over 108 days, comparing State-of-the-Art Practices (SoAP) with Coopetition Network Practices (CnP) supported by an IIoT-based system (Cockpit4.0+). Four manufacturing KPIs, First Time Through, Performance Efficiency, Raw Material Yield, and Labour Productivity, were assessed to evaluate operational improvements. The results show substantial gains in production output, material utilisation, labour productivity, and throughput, while maintaining product quality. These findings confirm that coopetition fosters innovation, optimises resource use, and enhances overall manufacturing efficiency in SMEs. Limitations include the focus on a single sector, short-term analysis, and the absence of financial and customer-related metrics. The study provides empirical evidence of the value of coopetition as a strategic approach for improving SME competitiveness. It highlights directions for future research on long-term impacts and the role of digital technologies in strengthening coopetition networks.